PORTRAIT OF STUDENTS’ CRITICAL THINKING ON WORK AND ENERGY MATERIALS - Aminah; Wawan Bunawan (Universitas Negeri Medan, 2025)
This research aims to develop a critical thinking test instrument on the material of work and energy that completes the aspects of validity, reliability, level of difficulty, item discrimination, and distractor effectiveness and maps students' critical thinking skills. The type of research used is quantitative research with the Research and Development method using the Tjeerd Plomp educational design research model integrated with the ADDIE development model with 5 stages, namely analysis, design, development, implementation, and evaluation. The instrument developed consists of 20 multiple-choice questions. The test sheet consists of multiple-choice physics test items arranged based on critical thinking indicators according to Facione. The results of the content validation test, according to material, construction, and language experts, obtained an average value of 0.97 with a high validity category. The validation results using the Cohen Kappa formula obtained a Kappa value of 0.63 with a